LANGUAGE OF PRIMARY SCHOOL STUDENTS FORMATION OF LEARNING ABILITIES INNOVATIVE METHODS - Saminjonova, Zuxraxon Xusanboy qizi (Educational Research in Universal Sciences, 2022)
This article discusses innovative ways to shape the language skills of primary school students and the role and importance of dictionaries in this process.